Radiographic evaluation of cardiac silhouette using vertebral heart size method in squirrel monkey (Saimiri sciureus) - Coutinho, L. N.; Brito, M. B.S. [UNESP]; Imbeloni, A. A.; Lacreta, A. C.C.; Rech, F.; Souto, M. P.; Ataíde, I. R.A. (Wiley, 2017)
Background: The Saimiri sciureus represents a valuable resource for biomedical research, due to its large number on primate centers and similarity to human anatomy and physiology. The aim of this study was to apply the method proposed by Buchanan & Bücheler in healthy squirrel monkeys (S. sciureus) and determine by radiographic examination, the average value of the vertebral heart size (VHS) for the specie. Method: Laterolateral left (LLL), laterolateral right (LLR), ventrodorsal (VD), and dorsoventral (DV) projections were used for radiographic examinations to evaluate the heart silhouette of S. sciureus. Results: There was no statistical difference between the projections LLL and LLR, or VD and DV, and between males and females, so measurements in the four radiographic projections were not performed. Conclusion: The values obtained in VHS of S. sciureus showed up species specific.
Keywords: cardiology; neotropical primates; radiology; thorax